Discharge distribution in a multi-outlet spillway with varying adverse conditions - Nils Solheim; Mikael P. A. Hedberg; Gunnar I. J. Hellström; Leif Lia; Anders G. Andersson; Patrik Andreasson; Elena Pummer (Scientific Reports)
Abstract Hydropower and dam structures worldwide are facing evolving requirements due to changes in climate, better methods for flood estimates, combined with the needs of surrounding interests. Improved understanding of the hydraulic behavior of spillways, and the approach flow leading up to them, is important for evaluation of existing spillways and considering potential redesigns. There is limited research on the distribution of flow across a multiple outlet spillway, therefore a purpose built experimental setup is utilized to examine the impact of various geometrical changes on the flow distribution across a spillway with three outlets. The maximum difference measured between the different outlets were as much as 10%. While small changes to abutment and pier corners were found to reduce total discharge capacity up to 8%, with increased discharge and overflow height causing greater reduction in the capacity of the spillway. To further investigate the flow behavior leading up to the spillway outlets, ADV measurements were conducted to capture flow velocities. The measured flow cross sections indicate a stable flow field leading away from the inlet, stagnation zones and recirculation zones leading up to the spillway, with minor variations occurring for increasing inlet flow rates.